Multi-Security System Based on RFID Fingerprint and Keypad to Access the Door - Ramses Wanto Tambunan; Abdul Aziz Ar-Rafif; Mia Galina (ELKHA : Jurnal Teknik Elektro, 2022)
It is necessary to prepare for the increasing crime rate of household theft with a modern home security system that allows customers to monitor home security remotely. This can be accomplished by replacing the standard lock with a solenoid door lock, which is more difficult to duplicate and reduces the likelihood of theft when the house is unoccupied. The Authors developed a three-tiered home security system prototype that includes fingerprint, the RFID, and keypad biometric sensors. The device's finished prototype was tested ten times after it was designed. The Arduino Uno microcontroller, which also serves as the door-locking mechanism, turns on the door-lock solenoid. When authentication is successful, someone will be granted access to the door. The preliminary findings indicate that the fingerprint. The fingerprint sensor's ability to read fingerprints in 3.7 seconds on average demonstrates its effectiveness. Second, the RFID sensor detects the e-KTP, and the RFID scans the card in an average of 2.4 seconds. The third keypad contains the password for unlocking the door. After ten repetitions, the experiment input yields an average time of 3.66 seconds. Opening a door with a 3-level multi-sensor typically takes 9.8 seconds. In this study, the installation of each sensor is notified via a GSM SIM800L module, allowing customers to monitor security remotely.